Building Landscapes : mending the fracture between cite' and ville through an urban architecture of place - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2019)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2019.